Modelling the influence of radiata pine log variables on structural lumber production - Gavilán, Elvis; Alzamora, Rosa M.; Apiolaza, Luis A.; Sáez, Katia; Elissetche, Juan Pedro; Pinto, Antonio (Maderas. Ciencia y Tecnología, 2022)
We run logit models to explain the variability of Pinus radiata structural lumber in 71 second and third unpruned logs. The response variable was the proportion of lumber with a static modulus of elasticity greater or equal than 8 GPa, pMSG8+, and the explanatory variables were log volume, branch index, largest branch, log internode index, wood basic density, and acoustic velocity. The average pMSG8+ volume was 44,30 % and 36,18 % in the second and third log respectively. Ten models were selected based on meeting statistical assumptions, their goodness of fit, and the statistical significance of their parameters. The best models (R2 - adj. > 0,75) included acoustic velocity (AV) as explanatory variable, which explained 56,25 % of the variability of pMSG8+. Models without AV presented goodness of fit ranging from 0,60 to 0,75 (R2 - adj.), and variables with the highest weight to explain the variability of pMSG8+ were volume, followed by wood basic density, branch index, and largest branch. It is possible to model pMSG8+ from log variables even when acoustic velocity is not available; however, this requires wood basic density models calibrated for the Pinus radiata growing zone.